To the notion of identity of the perpetrator of crimes in sphere of computer information (Journal of actual problems of jurisprudence, 2018)
Over the past ten years the Internet has become a virtual Playground, a place where people have the opportunity to Express ideas, to engage in social activities, etc. today, the Internet plays an important role in the field of communications: we conduct a variety of transactions with money, like using a computer, ATM, and other payment systems, the device calculates routes, looking for good restaurants, get to know us any interesting information. Of course, all these actions depend on information technology. The article investigates problems of computer information protection. Studied the personality of criminals in the field of information technology, victimological aspects of computer crimes.Key words: computer information, Internet, media hacker, computer literacy, crime.